Zebrafish Nutrition: Promoting Fish Health and Welfare of the Animal Model in Halal Science Research - Raja Idris, Raja Ibrah; MOHD TAUFEK, NORHIDAYAH; NORDIN, NOOR FAIZUL HADRY; AL-SAARI, NURHIDAYU (Halalsphere, 2022)
Zebrafish (Danio rerio) is a popular animal model in a variety of fields, including molecular biology, neurology, genetic research, aquaculture, and even halal science research. As the use of zebrafish in research grows, so does the need to focus on their welfare to ensure that they live in normal-good health, fit for research. Nutrition is an important but often overlooked welfare factor in zebrafish, as it affects their development, health, reproduction, and response to stimuli. In many modern laboratory settings, zebrafish feeding is dependent on the researcher, with numerous types of feed and feeding regimens used without a rigorous assessment of the fish growth. This is largely owing to a lack of information about zebrafish nutritional requirements, which is regarded as the most fundamental fault in any nutritional and growth study. A standard fish diet with an adequate amount of nutrition including the appropriate ratio of protein, carbohydrate, lipids, vitamins, and minerals are proposed to prevent the unplanned nutritional effect to the outcomes of such experiments. Protein is important for the growth of the fish while carbohydrates and lipid are the non-protein source of dietary energy for the fish diet. Feeds with the proper amount of dietary ingredients can help the fish live at optimum health. Islam teaches zero-tolerance to all forms of animal abuse throughout the halal production supply chain and although not many, there is a few number of demands on animal welfare as a purchase criterion. Therefore, as far as halal science is concerned, care must be taken to ensure the protection and welfare of laboratory animals utilized in research.